From Inert Storage to Biological Activity—In Search of Identity for Oxidized Cholesteryl Esters - Gonen, Ayelet; Miller, Yury I. (Frontiers in Endocrinology, 2020)
Esterification of cholesterol is a universal mechanism to store and transport large quantities of cholesterol between organs and tissues and to avoid toxicity of the excess of cellular cholesterol. Intended for transport and storage and thus to be inert, cholesteryl esters (CEs) reside in hydrophobic cores of circulating lipoproteins and intracellular lipid droplets. However, the inert identity of CEs is dramatically changed if cholesterol is esterified to a polyunsaturated fatty acid and subjected to oxidative modification. Post-synthetic, or epilipidomic, oxidative modifications of CEs are mediated by specialized enzymes, chief among them are lipoxygenases, and by free radical oxidation. The complex repertoire of oxidized CE (OxCE) products exhibit various, context-dependent biological activities, surveyed in this review. Oxidized fatty acyl chains in OxCE can be hydrolyzed and re-esterified, thus seeding oxidized moieties into phospholipids (PLs), with OxPLs having different from OxCEs biological activities. Technological advances in mass spectrometry and the development of new anti-OxCE antibodies make it possible to validate the presence and quantify the levels of OxCEs in human atherosclerotic lesions and plasma. The article discusses the prospects of measuring OxCE levels in plasma as a novel biomarker assay to evaluate risk of developing cardiovascular disease and efficacy of treatment.